PERILAKU RASIONAL POLITIK BIROKRASI DALAM PEMILU 2019 DI KABUPATEN BOALEMO - Ramli Mahmud; Asmun Wantu; Rasid Yunus; Yuli Adhani (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to analyze and identify factors that hinder the rational behavior of bureaucratic politics in the 2019 elections in Boalemo County. To answer this goal, this study uses qualitative methods with a phenomenological approach. The results showed that ASNs in the structural and functional ranks of teachers tend to behave irrationally in elections. Meanwhile, ASNs who are in the functional ranks of Health tend to be rational in making political choices. There are three factors that hinder ASN's political preferences in politically rational behavior, including familial and kinship factors or fraternal ties, the existence of regional heads as incumbents and the last is the motive factor for career offices. This is why asn tends not to be neutral in the 2019 elections in Boalemo County. Asn neutrality can be achieved if it behaves rationally in determining political choices consisting of logical considerations and consistency based on the vision, mission and work programs of both political parties and candidates.